Tom Swift and His Giant Cannon; Or, The Longest Shots on Record - Appleton, Victor (Salt Lake City, UT : Project Gutenberg, 1998)
"Tom Swift and His Giant Cannon; Or, The Longest Shots on Record" by Victor Appleton is a children$1 (Bs adventure novel written during the early 20th century. The story revolves around the extraordinary young inventor, Tom Swift, as he embarks on a daring quest to create the largest cannon ever built. The novel kicks off with an exciting mix of adventure and invention, highlighting Tom's ingenuity and determination to ensure the safety of the Panama Canal with his innovative weaponry. The opening of the book presents a lively scene where Tom's father, Mr. Swift, discusses a dubious investment proposal with an old acquaintance, Alec Peterson, regarding a lost opal mine. Amidst this business conversation, a frantic call for help arises when Tom finds himself in a perilous situation in his airship, entangled with a dangerous live wire. Thankfully, he is rescued by Peterson, which leads Mr. Swift to reconsider investing in the opal mine venture. Tom's character is further developed as he ponders his ambition to design a giant cannon for national defense, which he is keen to demonstrate at an upcoming government test for a similar cannon. This blend of high-stakes engineering, friendship, and the thrill of invention sets the stage for what promises to be a riveting adventure. (This is an automatically generated summary.)s
Release date is 1998-06-01
Produced by Anthony Matonac
Keywords: Adventure and adventurers -- Juvenile fiction; Swift, Tom (Fictitious character) -- Juvenile fiction; Ordnance -- Juvenile fiction